Enantioselective Additions of Stabilized Carbanions to Imines Generated from α-Amido Sulfones By Using Lipophilic Salts of Chiral Tris(1,2-diphenylethylenediamine) Cobalt(III) Trications as Hydrogen Bond Donor Catalysts - Joshi, Hemant; Ghosh, Subrata K.; Gladysz, John A. (Synthesis, 2017)
The enantiopure salt ∆-[Co((S,S)-dpen)3]3+ 2Cl–BArf– [BArf = B(3,5-C6H3(CF3)2)4] is an effective hydrogen bond donor catalyst (10 mol%, r.t., CH2Cl2) for enantioselective additions of dialkyl malonates to Boc-derivatized aryl imines generated from sulfones [ArCH(SO2Ph)NHBoc] in the presence of K2CO3 (ten examples, 91–97% isolated yields, 87–99% ee). The diastereomeric salt Λ-[Co((S,S)-dpen)3]3+ 2Cl–BArf20– [BArf20– = B(C6F5)4–] is similarly applied to additions of nitroalkanes (four examples, 89–93% isolated yields, 79–91% ee). Precautions to exclude air or moisture are unnecessary.
Keywords: Werner complexes; cobalt; 1,2-diamine ligands; chiral-at-metal complexes; hydrogen bonding; enantioselective catalysis; chiral benzylic amines; lipophilic anions